Propuesta de acompañamiento a la catequesis familiar de la parroquia “Nuestra señora de Fátima de la ciudad de Cuenca en el año 2013-2014” - Garzón Rodas, Mery Aidé (2014)
This present accompaniment proposal regarding the Family Catechesis of “Our Lady of Fatima,” is directed to guidance couples who work with the aforementioned parish, with the purpose to provide guidelines that will support the different subjects that they must teach to the parents of the family that attend the Catechesis once a week. This proposal consists of two guides; the first is a guide for the advisor of the Family Catechesis, that is, for its coordinating partner. This guide will be the foundation that will direct them concerning the issues to be dictated, and it contains a small description of the theme, the objectives and the development of the proposal. The second guide is the one for the workshop for each of the guidance couples where each of the dictated issues will be developed, the purpose of which is that it will work for the couple in order that it will also apply if it is considered necessary by the parents of the family.